Search for the Higgs Boson in the H→WW(*)→l +νl-ν̄ Decay Channel in pp Collisions at √s=7TeV with the ATLAS Detector - Aad, G; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; Abramowicz, H; Abreu, H; Acerbi, E; Acerbi, E; et al. (2012)
A search for the Higgs boson has been performed in the H→WW( *)→+ν-ν̄ channel (=e/μ) with an integrated luminosity of 2.05fb-1 of pp collisions at √s=7TeV collected with the ATLAS detector at the Large Hadron Collider. No significant excess of events over the expected background is observed and limits on the Higgs boson production cross section are derived for a Higgs boson mass in the range 110GeV